Investigating the impact of organised technology-driven orchestration on teaching - Phiri, Lighton (Department of Computer Science, 2019)
Orchestration of learning involves the real-time management of activities performed by educators in learning environments, with a particular focus on the effective use of technology. While different educational settings present unique problems, the common challenges have been noted to primarily be as a result of multiple heterogeneous activities and their associated intrinsic and extrinsic constraints. In addition to these challenges, this thesis argues that the complexities of orchestration are further amplified due to the ad hoc nature of the approaches and techniques used to orchestrate learning activities. The thesis proposes a streamlined approach to technology-driven orchestration of learning, in order to address these challenges and complexities. Specifically, the thesis proposes an organised approach that focuses on three core aspects of orchestration: activity management, resource management and sequencing of learning activities. Orchestration was comprehensively explored in order to identify the core aspects essential for streamlining technology-driven orchestration. Proof-of-concept orchestration toolkits, based on the proposed orchestration approach, were implemented and evaluated in order to assess the feasibility of the approach, its effectiveness and its potential impact on the teaching experience. Comparative analysis and guided orchestration controlled studies were conducted to compare the effectiveness of ad hoc orchestration with streamlined orchestration and to measure the orchestration load, respectively. In addition, a case study of a course that employed a flipped classroom strategy was conducted to assess the feasibility of the proposed approach. The feasibility was further assessed by integrating a workflow, based on the proposed approach, that facilitates the sharing of reusable orchestration packages. The results from the studies suggest that the streamlined approach is more effective when compared to ad hoc orchestration and has a potential to provide a positive user experience. The results also indicate that the approach imposes acceptable orchestration load during scripting of learning activities. Case studies conducted in authentic educational settings suggest that the approach is feasible, and potentially applicable to useful practical usage scenarios. The long-term implications are that streamlining of technology-driven orchestration could potentially improve the effectiveness of educators when orchestrating learning activities.